2023
DOI: 10.1101/2023.10.04.560807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ABCF proteins inEscherichia coliindividually alleviate nascent peptide-induced noncanonical translations

Yuhei Chadani,
Eri Uemura,
Kohei Yamazaki
et al.

Abstract: Organisms possess a wide variety of proteins with a diverse repertoire of amino acid sequences, and their synthesis relies on the ribosome. Empirical observations have led to the misconception that ribosomes are robust protein factories, but in reality, they have several weaknesses. For instance, ribosomes stall during the translation of the proline-rich sequences, but the translation elongation factor EF-P assists in synthesizing proteins containing the poly-proline sequences. Thus, living organisms have evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…However, it is possible that, like EF-P, Uup does not stimulate peptide bond formation between fMet-Phe, but may stimulate peptide bond formation between fMet and other amino acids (26, 29). Indeed, a recent preprint showed that Uup increased production of a peptide encoding a polyproline tract in vitro (67). Moreover, Uup-EQ2 has similar binding affinity for both initiating and elongating ribosomes (54), further suggesting that Uup may function in elongation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that, like EF-P, Uup does not stimulate peptide bond formation between fMet-Phe, but may stimulate peptide bond formation between fMet and other amino acids (26, 29). Indeed, a recent preprint showed that Uup increased production of a peptide encoding a polyproline tract in vitro (67). Moreover, Uup-EQ2 has similar binding affinity for both initiating and elongating ribosomes (54), further suggesting that Uup may function in elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in the case of aceB , the absence of a toeprint signal in the absence of EttA, juxtaposed with its presence in the presence of His 6 -EttA-EQ 2 , strongly suggests ribosome dissociation that can be stabilized by EttA-EQ 2 . This possible dissociation is further corroborated by a recent preprint in which the authors show that the introduction of three Glu residues at the beginning of the LacZ protein sequence triggers ribosome dissociation during in vitro synthesis, as evidenced by the formation of a peptidyl-tRNA, which can be rescued by EttA 58 . Secondly, for yjbJ , a distinct ribosome stalling event is observed, characterized by the detectable toeprinting signal.…”
Section: Mainmentioning
confidence: 57%
“…Ribosomal dissociation during elongation of acidic-residues has been previously demonstrated for MgtL and other proteins in prokaryotes 56,57 and eukaryotes 67 , this effect was described as Intrinsic Ribosome Destabilization (IRD). Moreover, a recent report suggest that EttA can prevent the IRD in vitro 55 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The importance to alleviate ribosome stalling at consecutive prolines is further underlined by the existence of additional rescue systems namely the A TP- B inding C assette family- F (ABCF) protein Uup in E. coli and its ortholog YfmR in B. subtilis 37,5961 . In interplay with EF-P, Uup/YfmR and EfpL can facilitate translation of XP(P)X containing proteins.…”
Section: Discussionmentioning
confidence: 99%